Determination of the correlation relationship of pedagogical tests of general physical training with a set of parameters describing the morphological features and canoeists. - Flerchuk Viktor Viktorovich; Soltyk Aleksandr Aleksandrovich (Kharkov National Pedagogical University, 2011)
Correlation connections of tests are certain to on general physical preparation with indexes morphological possibilities of sportsmen. 15 sportsmen took part in research. Propensity of sportsmen is set to certain distances in competition activity. Directions of selection and orientation of sportsmen are recommended to work of different orientation.